Why Who Cleans Counts : What Housework Tells Us about American Family Life - Davis, Shannon N.; Greenstein, Theodore N. (Book collections on Project MUSE., 2020)
Every household has to perform housework. Using quantitative, nationally representative survey data this book theorizes about how power dynamics as reflected in housework performance help us understand broader family variations.